Amino acid substitutions in antigenic region B of hemagglutinin play a critical role in the antigenic drift of subclade 2.3.4.4 highly pathogenic H5NX influenza viruses. Issue 1 (28th September 2019) - Li, Juan; Gu, Min; Liu, Kaituo; Gao, Ruyi; Sun, Wenqiang; Liu, Dong; Jiang, Kaijun; Zhong, Lei; Wang, Xiaoquan; Hu, Jiao; Hu, Shunlin; Liu, Xiaowen; et al.
Abstract: As one of the important control strategies for highly pathogenic avian influenza (HPAI) in China, vaccination has been implemented compulsively in poultry flocks since 2004. However, the emergence and dominance of the circulating antigenic variants require the update of vaccines periodically. In order to investigate the key molecular sites responsible for the antigenic drift, a total of 13 amino acid positions divergent between clade 2.3.4 H5 viruses and their descendent subclade 2.3.4.4 variants in or around the recognized antigenic epitopes A–E were initially identified through inspecting a comprehensive HA sequence alignment of the H5 subtype HPAI viruses. Subsequently, a panel of single‐site or multi‐site HA mutants was constructed by reverse genetics with two H5N1 viruses of S (clade 2.3.4) and QD1 (subclade 2.3.4.4) as the HA backbone to study their antigenic variations, respectively. The hemagglutination–inhibition assay revealed an evident impact of mutations at sites 88, 156, 205, 208, 239 and 289 to the HA antigenicity and highlighted that the amino acid substitutions located in the antigenic region B, especially the combined mutations at sites 205 and 208, were the major antigenic determinant which was also consistent with results from flow cytometry and antigenic mapping. Our findings provided more insights into the molecular mechanism of antigenic drift of the H5 subtype HPAI virus, which would be helpful for the selection of vaccine candidates and accordingly for the prevention and control of this devastating viral agent.